Trace gases, aerosols, and solar radiation in the stratosphere -- explored and unexplored problem areas - Reiter, Elmar R., author; American Institute of Aeronautics and Astronautics, publisher (Colorado State University. Libraries, 1973)
The Climatic Impact Assessment Program (CIAP) of the Department of Transportation is--among other things--faced with the task of providing a detailed review of the "undisturbed" stratosphere as it exists before the commencement of SST traffic. CIAP Monograph No. 1, presently in preparation, deals with this "natural stratosphere." Material for a rough draft of this volume was compiled by approximately 90 scientists during a workshop in Ft. Lauderdale from November 28 through December 1, 1972. This short review paper, based upon the draft of CIAP Monograph No. 1, points out the highlights of our present knowledge of the stratosphere, especially with respect to the O3, NOx and H2O problems, and also explores some of the deficiencies in this knowledge which will have to be overcome before a complete assessment of human impact on this atmospheric region can be made.
Presented at the AIAA/AMS international conference on the environmental impact of aerospace operations in the high atmosphere held in Denver Colorado on June 11-13, 1973.
Keywords: Upper atmosphere -- Congresses; Nature -- Effect of human beings on -- Congresses